A Pilot Study to Locate Historic Scientific Data in a University Archive - Shannon Farrell; Julia Kelly; Lois Hendrickson; Kristen Mastel (Issues in Science and Technology Librarianship)
Historic data in analog (or print) format is a valuable resource that is utilized by scientists in many fields. This type of data may be found in various locations on university campuses including offices, labs, storage facilities, and archives. This study investigates whether biological data held in one institutional university archives could be identified, described, and thus made potentially useful for contemporary life scientists. Scientific data was located and approximately half of it was deemed to be of some value to current researchers and about 20% included enough information for the study to be repeated. Locating individual data sets in the collections at the University Archives at the University of Minnesota proved challenging. This preliminary work points to possible ways to move forward to make raw data in university archives collections more discoverable and likely to be reused. It raises questions that can help inform future work in this area.